2022
DOI: 10.3390/agriculture12030313
|View full text |Cite
|
Sign up to set email alerts
|

Green Finance, Chemical Fertilizer Use and Carbon Emissions from Agricultural Production

Abstract: This study aimed to understand green finance’s impact on fertilizer use and agricultural carbon emissions. We selected the macro panel data of 30 provinces (cities) in China from 2000 to 2019. The main research methods are standardized test framework (cross-sectional dependence, unit root and cointegration test), the latest causal test, impulse response, and variance decomposition analysis. Examined the long-term equilibrium relationship between green finance, fertilizer use, and agricultural carbon emissions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 52 publications
0
53
0
Order By: Relevance
“…20% of the energy consumption can be saved if the DMU’s value equals 80% ( Xiong and Sun, 2022 ). An assessment of energy and environmental techniques ( Guo et al, 2022 ) is the sole focus of this article. For example, the efficiency of energy-related emissions is measured by Li et al (2022) .…”
Section: Methodology and Datamentioning
confidence: 99%
“…20% of the energy consumption can be saved if the DMU’s value equals 80% ( Xiong and Sun, 2022 ). An assessment of energy and environmental techniques ( Guo et al, 2022 ) is the sole focus of this article. For example, the efficiency of energy-related emissions is measured by Li et al (2022) .…”
Section: Methodology and Datamentioning
confidence: 99%
“…Agricultural production activities produce a large amount of greenhouse gases, and their impact is second only to industrial carbon emissions, making agricultural emission reductions imperative (Scuderi et al, 2021). Scholars have used Kaya constant equation, LMDI factor decomposition, STIRPAT model, Divisia index decomposition, ARDL model, VAR model, and GWR model to study the factors influencing agricultural carbon emissions (Li et al, 2014;Akram et al, 2019;Aziz et al, 2022;Yan et al, 2017;Koondhar et al, 2021;Guo et al, 2022;Han et al,2021). It was found that agricultural economic growth, the degree of agricultural disaster, the increase of GDP per capita and energy intensity have a certain promotion effect on agricultural carbon emissions, while factors such as agricultural technological progress, the structure and production efficiency of cropping industry, urbanization process, the size of agricultural labor force, the agglomeration of agricultural industry and the level of agricultural mechanization have a certain inhibiting effect on agricultural carbon emissions (Deng et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Household energy consumption and agricultural production are the two main sources of carbon emissions [ 1 , 2 ]. The long-term use of non-clean energy by households and traditional agricultural production practices produces large amounts of greenhouse gases, which are a major cause of frequent climate extremes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%